Crossing the strait : Morocco, Gibraltar and Great Britain in the 18th and 19th centuries - Brown, James A. O. C. (Studies in the History and Society of the Maghrib, 2012)
The Strait of Gibraltar is a ubiquitous symbol of the supposed dividing line between Europe and the Muslim world. This book re-evaluates that perception with reference to new archival evidence about the links between the Gharb region of Morocco and Gibraltar and the establishment of the Moroccan consulate there, focusing on the period around 1750-1850. It shows the development of a complex set of political, social and economic relationships across the strait that connected Morocco to Gibraltar and beyond. In the light of this evidence, the book challenges prevailing arguments that emphasise the isolationist impulses of the Moroccan sultanate and Moroccan society, and highlights the extent to which European expansion in this period was shaped by local responses.